Esculturas africanas de Chile: lecturas de un patrimonio nacional en el escenario de la diferencia cultural - Carmona Jiménez, Javiera Antonia (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
Since 1930 the Chilean sculptural heritage has a set of African sculptures that belonged to the avant-garde poet Vicente Huidobro. The foundational temporality of this heritage is examined, understood as the contexts of initial collection of the pieces within the framework of the European avant-gardes, the acquisition by the Chilean State and the first exhibition of the pieces by the National Museum of Fine Arts of Chile. The revision of this first temporality links the work and ideology of Huidobro with his sculptures and with the construction of knowledge and ideas about the cultural difference affirmed and expressed by state museums attuned to the legacy of European colonialism in Latin America and the emancipatory artistic and political movements, critical of Eurocentrism of the elites. This stage of the patrimonialization process of the African sculptures that finally became Chilean sculptural heritage, reveals the state museums as legitimate agents of the symbolic dispute for the construction of patrimonial sense around the cultural diversity. This challenge of the museums is relevant in the current Chilean context of the XXI century of intensification of the migratory flows that confront the Chilean society with itself before “the black”, “the afro”, “the other”.